Numerical Simulation of Two-Phase Flows in Heterogeneous Porous Media - Carneiro, I.; Borges, M.; Malta, S. (Trends in Computational and Applied Mathematics, 2020)
In this work,we present three-dimensional numerical simulations of water-oil ﬂow in porous media in order to analyze the inﬂuence of the heterogeneities in the porosity and permeability ﬁelds and, mainly, their relationships upon the phenomenon known in the literature as viscous ﬁngering. For this, typical scenarios of heterogeneous reservoirs submitted to water injection (secondary recovery method) are considered. The results show that the porosity heterogeneities have a markable inﬂuence in the ﬂow behavior when the permeability is closely related with porosity, for example, by the Kozeny-Carman (KC) relation.This kind of positive relation leads to a larger oil recovery, as the areas of high permeability(higher ﬂow velocities) are associated with areas of high porosity (higher volume of pores), causing a delay in the breakthrough time. On the other hand, when both ﬁelds (porosity and permeability) are heterogeneous but independent of each other the inﬂuence of the porosity heterogeneities is smaller and may be negligible.